2005
DOI: 10.1161/01.hyp.0000173433.67426.9b
|View full text |Cite
|
Sign up to set email alerts
|

Blood Pressure in Adulthood and Life Expectancy With Cardiovascular Disease in Men and Women

Abstract: Abstract-Limited information exists about the consequences of hypertension during adulthood on residual life expectancy with cardiovascular disease. We aimed to analyze the life course of people with high blood pressure levels at age 50 in terms of total life expectancy and life expectancy with and without cardiovascular disease compared with normotensives. We constructed multistate life tables for cardiovascular disease, myocardial infarction, and stroke using data from 3128 participants of the Framingham Hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
138
0
8

Year Published

2007
2007
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 243 publications
(156 citation statements)
references
References 19 publications
4
138
0
8
Order By: Relevance
“…38 Clinical implications HPT is an important risk factor associated with all-cause and cardiovascular mortality, as well as a greater life expectance without cardiovascular disease. 2,47 Moreover, BP is strong and linearly associated with coronary heart disease and stroke, 2 which are the most common causes of mortality among women. 48 Preventing or delaying the onset of HPT may therefore have a large impact on public health, mainly in individuals at high risk for HPT.…”
Section: Study Limitationsmentioning
confidence: 99%
“…38 Clinical implications HPT is an important risk factor associated with all-cause and cardiovascular mortality, as well as a greater life expectance without cardiovascular disease. 2,47 Moreover, BP is strong and linearly associated with coronary heart disease and stroke, 2 which are the most common causes of mortality among women. 48 Preventing or delaying the onset of HPT may therefore have a large impact on public health, mainly in individuals at high risk for HPT.…”
Section: Study Limitationsmentioning
confidence: 99%
“…Although the high levels of selfreported DM and hypertension control likely reflect a certain degree of subjective reporter bias, our findings support that HRS participants with these conditions are generally under good control; DM and hypertension were associated with only moderate levels of increased risk for mortality and cardiovascular events compared with hazard ratios previously reported for uncontrolled disease. 20, [40][41][42] Other studies evaluating a subset of HRS respondents also found similar moderately increased risks for DM and hypertension. 43,44 *Low and high were determined by whether scores were below or at least equal to the median, respectively † Discrete time-to-event model included psychological groups (based on perceived constraints and health-specific control), main biomedical predictors (diabetes and hypertension), perceived mastery (in quartiles), self-reported heart disease, lung disease, cancer, psychological problems, arthritis, memory difficulties, baseline smoking, vigorous activity more than once a week, difficulty with activities of daily living (ADLs) or instrumental activities of daily living (IADLs), score on the 8-question Centers of Epidemiologic Studies Depression Scale (CESD8), and scores for positive and negative affect; see Methods for full variable definitions ‡ Rate calculated as number of events per 1,000 person-years of follow-up In addition to variables in the basic model, the full model includes self-reported heart disease, lung disease, cancer, psychological problems, arthritis, memory difficulties, baseline smoking, vigorous activity more than once a week, difficulty with activities of daily living (ADLs) or instrumental activities of daily living (IADLs), score on the 8-question Centers of Epidemiologic Studies Depression Scale (CESD8), and scores for positive and negative affect; see Methods for full variable definitions…”
Section: Discussionmentioning
confidence: 81%
“…After age 55, women have equal or greater prevalence of HTN compared with men 2. Life expectancy for women with HTN is on average 4.9 years shorter than women with normal blood pressure (BP) at the age of 50 3. The prevalence of HTN among black women in the United States is one of the highest in the world, at more than 40% 1.…”
Section: Introductionmentioning
confidence: 99%